Non-Invasive Low Power ECG for Heart Beat Detection of Bats - Duda, Niklas; Barthule, Alexander; Ripperger, Simon; Mayer, Frieder; Weigel, Robert; Kölpin, Alexander (2019 IEEE Topical Conference on Wireless Sensors and Sensor Networks (WiSNet), 2019)
In this paper a small size low power electrocardiogram (ECG) system which is optimized for the heart rate detection of bats is proposed. Due to the smaller size and different physical properties of animals like bats the system has to fulfill different requirements than standard human ECGs. The usecase of animal monitoring also requires an ultra-low power approach to enable long battery runtime. The described system has been evaluated with measurements on bats and compared to a commercially available ECG integrated circuit (IC). Apart from the ECG circuit itself the electrodes and the electrode position as well as the used algorithms are evaluate